2000
DOI: 10.3109/08830180009088516
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ Disease: A Host Defense Mechanism Gone Awry

Abstract: In this report we summarize evidence to support a model for the development of Graves' disease. The model suggests that Graves' disease is initiated by an insult to the thyrocyte in an individual with a normal immune system. The insult, infectious or otherwise, causes double strand DNA or RNA to enter the cytoplasm of the cell. This causes abnormal expression of major histocompatibility (MHC) class I as a dominant feature, but also aberrant expression of MHC class II, as well as changes in genes or gene produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…Firstly, the Shimojo model supports the hypothesis proposed by Bottazzo et al more than two decades ago [25] that has since been evaluated extensively by others [26]. In their hypothesis, thyroid cells in autoimmune thyroid diseases aberrantly express MHC class II antigen and, as non-professional antigen-presenting cells, present thyroid-specific autoantigens to naïve T cells, leading to thyroid autoimmune reaction.…”
Section: Implications Of Animal Models In Disease Pathogenesissupporting
confidence: 63%
“…Firstly, the Shimojo model supports the hypothesis proposed by Bottazzo et al more than two decades ago [25] that has since been evaluated extensively by others [26]. In their hypothesis, thyroid cells in autoimmune thyroid diseases aberrantly express MHC class II antigen and, as non-professional antigen-presenting cells, present thyroid-specific autoantigens to naïve T cells, leading to thyroid autoimmune reaction.…”
Section: Implications Of Animal Models In Disease Pathogenesissupporting
confidence: 63%
“…Cytotoxic T cells such as NK cells could have an early regulatory role in innate and adaptive immunity. HLA class I molecules are recognized by NK cells through killer immunoglobulin-like receptors (KIR) [17,18]. Recent studies have indicated that an HLA-class I/KIR complex is associated with the pathogenesis and susceptibility of type-1 diabetes mellitus [19,20,21], psoriatic arthritis [22], ankylosing spondylitis [23], hepatitis B [24], and hepatitis C [25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 90K induces MHC class I expression (15,16), and the concomitant suppression of both 90K and MHC class I by TSH has been suggested as a mechanism to preserve selftolerance and prevent autoimmunity (16,25,26,28). On the basis of these considerations, we suggest that induction of 90K by USFs may be another mechanism through which these transcription factors activate immune responses.…”
Section: Discussionmentioning
confidence: 91%